Tradition of Urdu Translation of the Holy Quran; An overview of Causes and Motivations. - Hafiz Muhammad Tahir Mustafa; Hafiz Qamar Iqbal (jihat-ul-islam, 2021)
In the Indian subcontinent, the first complete translation of the Holy Quran was written in the 19th century. Subsequently, several translations appeared in the epistemic sphere. It encouraged academics to provide their scholarly opinion about them. Comparing different translations, they drafted both books and articles on their introduction, history, and importance. However, the reasons behind their emergence are overlooked. Mainly using an analytical approach, the present study tried to find out the main objectives of the translators. For this purpose, this paper studies the methodology mentioned in the prefaces and adopted while translating. It is argued that the emergence of these translations was not only part of a noble practice but also there were several other reasons behind it. It includes the development of Urdu language, the existence of abandoned words and abbreviations in the translation works, the lexical and legal objections in previous translations, new interpretations, easiness for like-minded people, and satisfaction of the taste of the translator. In the light of this study in present era, It will be easy to find out the gape and justify the new translation of the Holy Quran.